2021
DOI: 10.3390/ijms22042182
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Ephrins on Immune Cells of Patients with Relapsing Remitting Multiple Sclerosis Affects Oligodendrocyte Differentiation

Abstract: The effect of the inflammatory response on regenerative processes in the brain is complex. This complexity is even greater when the cause of the tissue damage is an autoimmune response. multiple sclerosis (MS) is an immune-mediated disease in which demyelination foci are formed in the central nervous system. The degree of repair through oligodendrocyte regeneration and remyelination is insufficient. Ephrins are membrane-bound ligands activating tyrosine kinase signaling proteins that are known to have an inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…For example, it has recently been reported that Epstein-Barr virus (EBV) infection dramatically increases the odds of developing multiple sclerosis, 47 and while this has been attributed to molecular mimicry between EBV and the glial cell adhesion molecule (GlialCAM) that is the target of autoantibodies, 48,49 it can also be speculated that the GlialCAM peptide(s) might be able to form a complex with viral proteins and the entry receptor (Eph and Eph-receptor binding proteins, ephrins). 50 In conclusion, the results from the study presented here point to a new understanding of some aspects of the pathogenesis of SSc and autoimmune diseases that could have diagnostic and therapeutic implications to assess with subsequent work.…”
Section: Discussionmentioning
confidence: 68%
“…For example, it has recently been reported that Epstein-Barr virus (EBV) infection dramatically increases the odds of developing multiple sclerosis, 47 and while this has been attributed to molecular mimicry between EBV and the glial cell adhesion molecule (GlialCAM) that is the target of autoantibodies, 48,49 it can also be speculated that the GlialCAM peptide(s) might be able to form a complex with viral proteins and the entry receptor (Eph and Eph-receptor binding proteins, ephrins). 50 In conclusion, the results from the study presented here point to a new understanding of some aspects of the pathogenesis of SSc and autoimmune diseases that could have diagnostic and therapeutic implications to assess with subsequent work.…”
Section: Discussionmentioning
confidence: 68%
“…Prior research has also shown that EPH-ephrin signaling is more prevalent in relapsing-remitting multiple sclerosis than in other subtypes of the disease 44 . EPH-ephrin signaling survived FDR correction in our analysis (Figure 3 (c)).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in transcriptional regulation are thought to be linked to modifications in OLG heterogeneity (Falcão et al, 2018; Jäkel et al, 2019) and inefficiencies in OLG maturation and myelin repair (Chang et al, 2002; Duncan et al, 2017; Kuhlmann et al, 2008). As cause for such dysregulated gene expression in OLGs, recent evidence points to the actions of extrinsic factors rather than intrinsic OLG defects (Golan et al, 2021; Kirby et al, 2019; Mozafari et al, 2020; Saraswat et al, 2021; Starost et al, 2020). Thus, targeting druggable signaling pathways with the capacity to modulate gene expression profiles associated with OLG maturation has emerged as a promising approach toward promoting repair of the myelin sheath in MS (Angelini et al, 2021; Gaesser & Fyffe‐Maricich, 2016; Göttle et al, 2019; Green et al, 2017; Jeffries et al, 2016, 2021; Lecca et al, 2020; Mausner‐Fainberg et al, 2021; Mierzwa et al, 2013; Petersen et al, 2021; Rajendran et al, 2021; Roggeri et al, 2020; Skinner & Lane, 2020; Thümmler et al, 2019; Wang et al, 2020; Welliver et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As cause for such dysregulated gene expression in OLGs, recent evidence points to the actions of extrinsic factors rather than intrinsic OLG defects (Golan et al, 2021;Kirby et al, 2019;Mozafari et al, 2020;Saraswat et al, 2021;Starost et al, 2020).…”
mentioning
confidence: 99%